The Tell-Tale Brain : unlocking the mystery of human nature - V S Ramachandran (Random House, 2010)
* A patient in San Francisco becomes progressively demented, yet starts creating paintings that are hauntingly beautiful. Has his brain damage somehow unleashed a hidden talent? Is there a Picasso, a Mozart, and a Ramanujan in all of us? * \'Who is this woman in the mirror who is always following me?\' asks a woman whenever she sees her reflection in the mirror. Like vampires, she is terrified of mirrors. Why? * Whenever Shirley looks at a number she sees it tinged with a particular colour; 5 is red, 2 is green, etc. This condition called synesthesia is eight times more common in artists, poets, and novelists suggesting that it may be linked to creativity in some mysterious way. The brain remains a mystery to us. How can a three pound mass of jelly that we can hold in our palm imagine angels, contemplate the meaning of infinity, and even question its own place in the cosmos? How can one study such a mystery? Eminent neuroscientist Professor V.S. Ramachandran takes us on a fascinating journey into the human brain, studying patients who exhibit bizarre symptoms, and using them to understand the functions of the normal brain. Along the way he asks big questions: How did abstract thinking evolve? What is art? Why do we laugh? How are these hardwired in the neural mechanisms of the human brain, and why did they evolve? Brilliant, lucid, and utterly compelling, The Tell-Tale Brain is a pathbreaking book from one of the leading neuroscientists today.